Cecília Meireles: crônicas de arte, cultura e educação - Silva, Mariana Batista do Nascimento (2008)
This research aims to identify, analyze and discuss some of Cecília Meireles conceptions about art and culture in the educational system using her chronicles published in Diário de Notícias newspaper in the 1930 decade in Rio de Janeiro. So we have established relations among chronicle, journalism, history and literature, four knowledge areas related to our corpus. Chronicle, a memory s place, has allowed us a glimpse of not only Meireles thoughts about 1930 decade s art and culture, but also her personal historical version of 1930. It was necessary to take note of some gatherings in which Meireles had taken part such as Movimento dos Pioneiros da Educação and her relation to the modernist ideas and the literary and educational influences in her professional identity. Thus, we could identify cultural and artistic elements in the school and society, in general terms, according to the poetess, educator and journalist Cecília Meireles writings.